Noninvasive mechanical ventilation [Noninvazif mekanik ventilasyon] - (:unkn) unknown (Marmara University, 2011)
Respiratory failure in patients hospitalized in the intensive care unit is a common clinical problem. These patients need respiratory support until the effect of medical treatment begins. Positive pressure ventilation is used to support patients with respiratory failure. Mechanical ventilatory support may be given to the patient via face interface during noninvasive mechanical ventilation (NIMV) or via entubation tube during invasive mechanical ventilation (IMV). Although the degree of support are the same, complication rates are lower in NIMV than IMV.
Keywords: Breathing; Noninvasive mechanical ventilation